Literacy Training at Sekolah Impian in Savanna Village: Cultivating Knowledge for a Brighter Future - Febrianti, Riska (IJOCSE: Indonesian Journal of Community Services, 2024)
Literacy plays a crucial role in shaping students’ academic abilities and future success. However, English literacy levels among elementary students in Kampung Savana remain underdeveloped due to limited access to proper learning facilities. This community service program aimed to enhance English literacy skills among children at Sekolah Impian through structured training activities. The program was conducted in two stages: preparation and implementation. The preparation stage involved site visits, participant selection, and material development, while the implementation stage included material delivery, reading practice, and an engaging ice-breaking session. The main focus was on the theme "Location and Direction" to strengthen students’ spatial and linguistic understanding. The results indicated that students actively participated in the learning process, demonstrating enthusiasm and confidence in engaging with the provided materials. The ice-breaking activity further fostered an enjoyable learning environment, making English literacy training more effective. This initiative highlights the importance of early literacy education and calls for continued efforts to support English learning in underprivileged communities.